IMMU-08. Nivolumab with or without ipilimumab in pediatric patients with high-grade CNS malignancies: efficacy, safety, biomarker, and pharmacokinetic results from Checkmate 908. (3rd June 2022) - Dunkel, Ira J; Cohen, Kenneth; Foreman, Nicholas K; Hargrave, Darren; Lassaletta, Alvaro; André, Nicolas; Hansford, Jordan R; Hassall, Tim; Eyrich, Matthias; Gururangan, Sridharan; Bartels, Ute; Gajjar, Amar; et al.
Abstract: BACKGROUND: Limited data exist regarding checkpoint inhibitor efficacy for pediatric CNS malignancies. METHODS: CheckMate 908 is an open-label, sequential-arm, phase 1b/2 study investigating nivolumab (NIVO) and NIVO + ipilimumab (IPI) in 5 cohorts of pediatric patients previously treated with standard-of-care (NCT03130959). Patients received NIVO-3mg/kg Q2W or NIVO-3mg/kg + IPI-1mg/kg Q3W (4 doses) followed by NIVO-3mg/kg Q2W. Primary endpoints included OS (newly diagnosed DIPG) and PFS (other CNS cohorts); secondary endpoints included other efficacy metrics/safety. Exploratory endpoints included pharmacokinetics/biomarker analyses. Comparisons between treatments/cohorts were not planned. RESULTS: At data cutoff (13-Jan-2021), 166 patients received NIVO (n=85) or NIVO+IPI (n=81) at median (m) ages of 10.0yrs (range, 1-21) and 11.0yrs (1-21), respectively. In newly diagnosed DIPG, mOS (80% CI) was 11.7mos (10.3-16.5) with NIVO (n=23) and 10.8mos (9.1-15.8) with NIVO+IPI (n=22). In recurrent/progressive HGG, mPFS (80% CI) was 1.7mos (1.4-2.7) with NIVO (n=16) and 1.3mos (1.2-1.5) with NIVO+IPI (n=15). In relapsed/resistant medulloblastoma, mPFS (80% CI) was 1.4mos (1.2-1.4) with NIVO (n=15) and 2.8mos (1.5-4.5) with NIVO+IPI (n=15). In relapsed/resistant ependymoma, mPFS (80% CI) was 1.4mos (1.4-2.6) with NIVO (n=12) and 4.6mos (1.4-5.4) with NIVO+IPI (n=10). In other recurrent/progressive CNS tumors, mPFS (95% CI) was 1.2mos (1.1-1.3) with NIVO (n=19) and 1.6mos (1.3-3.5) with NIVO+IPI (n=19). Median treatment duration was 2.1mos (range, 0-41.7+ [NIVO]/0-29.6+ [NIVO+IPI]). Grade 3/4 treatment-related AEs occurred in 14.1% (NIVO) and 27.2% (NIVO+IPI) of patients. NIVO and IPI first dose trough concentrations were lower in youngest and lowest-weight patients. Baseline tumor PD-L1 expression was not associated with survival. Tumor mutational burden was high in 1 patient (NIVO+IPI) with HGG (OS=11.0mos). CONCLUSIONS: NIVO±IPI demonstrated no clinical benefit in pediatric patients with high-grade CNS malignancies, consistent with available historical data. The safety profiles were manageable.